Front Cover: Orthogonal Peptide‐Templated Labeling Elucidates Lateral ETAR/ETBR Proximity and Reveals Altered Downstream Signaling (ChemBioChem 6/2022). (5th November 2021) - Wolf, Philipp; Mohr, Alexander; Gavins, Georgina; Behr, Victoria; Mörl, Karin; Seitz, Oliver; Beck‐Sickinger, Annette G.
Abstract : Elucidation of protein interactions in living cells is a critical step in deciphering pharmacological targets. Here, we apply an orthogonal labeling approach to G protein‐coupled receptors by two peptide pairs, interacting through coiled‐coil motifs. The rapid reporter introduction in a one‐pot reaction allows the investigation of transient and proximity‐dependent interplay of different receptor proteins at the cell membrane. Focusing on prominent cardiovascular receptors, present in heart and blood vessel tissue, distinct receptor–receptor interactions have been identified that modulate intracellular signaling cascades. More information can be found in the Full Paper by A. G. Beck‐Sickinger et al.